Assessment of organochlorine pesticides and plasticisers in the Selangor river basin and possible pollution sources - Santhi, V.A.; Mustafa, A.M. (2013)
A study on the quality of water abstracted for potable use was conducted in the Selangor River basin from November 2008 to July 2009. Seven sampling sites representing the intake points of water treatment plants in the basin were selected to determine the occurrence and level of 15 organochlorine pesticides (OCPs), six phthalate esters (PAEs) and bisphenol A (BPA). Results indicated OCPs were still detected regularly in 66.1 of the samples with the I (15)OCPs pound ranging from 0.6-25.2 ng/L. The first data on PAEs contamination in the basin revealed I (6)PAEs pound concentrations were between 39.0 and 1,096.6 ng/L with a median concentration of 186.0 ng/L while BPA concentration ranged from < 1.2 to 120.0 ng/L. Although di-n-butyl phthalate was detected in all the samples, concentrations of di-ethyl(hexyl)phthalate were higher. Sampling sites located downstream recorded the highest concentrations, together with samples collected during the dry season. Comparison of the detected contaminants with the Department of Environment Water Quality Index (DOE-WQI) showed some agreement between the concentration and the current classification of stream water. While the results suggest that the sites were only slightly polluted and suitable to be used as drinking water source, its presence is cause for concern especially to the fragile firefly "Pteroptyx tener" ecosystem located further downstream.